WAYS TO INCREASE USE OF INTERNATIONAL AIR LINES IN MODERN CONDITIONS OF WORLD CIVIL AVIATION - Бугайко, Д. О.; Похилено, К .О. (Science-based technologies, 2009)
Modern trends in the world civil aviation development are considered in the article. The ways of efficiency in-crease of international airlines exploitation in modern conditions are analysed.